The Development of New Media in the Economic Growth of the Indonesian Music Industry - Isra Ruddin; Jamalullail Jamalullail (Yayasan Ilomata, 2022)
This study will discuss how new media in the music industry affect the music industry. This has had a major impact on businesses in the music industry and consumers who enjoy music. Streaming services have become something that has a big impact in the digital era that we know as Industry 4.0. The music industry can no longer rely on physical products and consumers are increasingly choosing to enjoy music. The method used in this research is a good method that is tested through research with unusual research ideas about; Describe behavior, thoughts, motivations, actions, etc. in the aggregate and in the form of words and messages. The findings of this study are that consumers find music easier and industry players support new media in the music industry because it makes it easier for them to market music and helps protect their intellectual property thereby reducing piracy. Market participants can also use the appropriate marketing mix. Luggage; Good recording, good songwriting should be distributed and rewarded; Because in the digital era, there are many streaming applications that must be used properly, such as uploading works to social media and streaming applications, so that uploaded works can be supported by Monetization.